2018
DOI: 10.1001/jamaophthalmol.2017.5978
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Electronic Health Records and Perceptions of Financial and Clinical Outcomes Among Ophthalmologists in the United States

Abstract: Assessing the rate of electronic health record (EHR) adoption and ophthalmologists' perceptions on financial and clinical productivity is important in understanding how to direct future design and health care policy. OBJECTIVE To assess adoption rate and perceptions of financial and clinical outcomes of EHRs among ophthalmologists in the United States. DESIGN, SETTING, AND PARTICIPANTS Population-based, cross-sectional study. A random sample of 2000 ophthalmologists was generated on the basis of mailing addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 15 publications
0
49
0
Order By: Relevance
“…7,8 As a result, ophthalmologists often report feeling pressured to see more patients to maintain revenue, while having less available time for patient care. [9][10][11] Without approaches to manage these pressures, the situation may become untenable and result in decreased quality of care and physician burnout. 12,13 Reducing clinic inefficiencies can help physicians manage these pressures.…”
Section: Précismentioning
confidence: 99%
“…7,8 As a result, ophthalmologists often report feeling pressured to see more patients to maintain revenue, while having less available time for patient care. [9][10][11] Without approaches to manage these pressures, the situation may become untenable and result in decreased quality of care and physician burnout. 12,13 Reducing clinic inefficiencies can help physicians manage these pressures.…”
Section: Précismentioning
confidence: 99%
“…A body of studies have addressed concerns about factors associated with the adoption of EHRs among general hospitals, nursing homes, 19,20 office settings, 21 cancer hospitals, 22 critical-access hospitals, 23 obstetrician/gynecologists, 24 and ophthalmologists. 25 Commonly included factors are initial cost of implementing a system, 19,20,23,[26][27][28][29][30][31] maintenance/ ongoing costs, 19,27,30,32 financial incentives, 20,23,24,33 technical support, 19,20,23,26,28,30 privacy concerns, 19,21 perception of hospital staff, 24,28,[31][32][33][34] and workload/workflow change. 20,23,24,26,30,33 Factors concerning facility characteristics have also been mentioned, such as practice setting, 35 teaching status, 36 system affiliation,…”
Section: Introductionmentioning
confidence: 99%
“…Incentives and mandates within the passage of the Health Information Technology for Economic and Clinical Health (HITECH) Act of 2009, 5,6 have led to the adoption of EHRs as an essential technology for most U.S. medical practices, including ophthalmology practices. 7 While this technology has the potential to increase efficiency and decrease the cost of medical documentation and patient information retrieval, 6 use of EHR has been shown to affect the visual, verbal, and postural connection between internal medicine clinicians and patients. 8 It has also been shown that patients believed exam room computers decreased the amount of interpersonal contact with internal medicine physicians.…”
mentioning
confidence: 99%
“…A 2018 survey of the American Academy of Ophthalmology members found that 72% of practices surveyed had implemented EHRs, but found that many ophthalmologists perceived a decrease in patients seen per day and a need for increased EHR usability. 7 These perceptions are warranted as several studies on the efficiency of EHR use for ophthalmologists show that EHR documentation is slower than paper charting. [10][11][12] However, the impact of EHR on the patient-provider relationships needs further investigation.…”
mentioning
confidence: 99%